EUS-guided intra-tumoral therapies. (September 2022) - Marc, Barthet; Monino, Laurent; Rimbas, Mihai
Abstract: EUS-guided treatments for focal tumor lesions has been developed since 20 years using at onset of the technique mainly local and guided alcohol injection [1-4]. Pancreatic tumors are the most assessed targeted lesions for EUS treatment because of their accessibility and because EUS management could be a safe alternative to surgery. More and more pancreatic tumors are discovered mainly fortuitously due to the advances in conventional imaging (abdominal ultrasound, CT, MRI) resulting in the question of surgical management of an asymptomatic pancreatic lesion ("incidentaloma") [5–8]. The lesions detected include mostly pancreatic cystic neoplasms (PCN) and neuroendocrine tumors (NET) mainly well differentiated. Clinically, NET are mostly non-functional and do not induce secretory disorders [5–8]. Once their nature is yielded by diagnostic tests like EUS-FNA, incidental nonfunctional NET currently lead to difficult management when their largest diameter is less than 2 cm [2, 4, 9, 10]. EUS-guided treatment for pancreatic adenocarcinoma have also been developed with recent prospective observational study and randomized control study [11, 12]. Thus, therapeutic surgical choices could be challenged by EUS- guided treatment [2, 4, 9].